MODERNISASI DAN TERBENTUKNYA GAYA HIDUP ELIT EROPA DI BRAGAWEG (1894-1949) - Hary Ganjar Budiman (Balai Pelestarian Nilai Budaya Jawa Barat, 2017)
This study describes the Bragaweg changes from 1894 to 1949. In addition, this study describes the form of European-style activity in Braga Street that represents the modern nuances of the colonial period. The historical method is used to construct the Braga story. To support the analysis of this study, the author uses the concept of modernization of Lawrence V. Stockman. He stated that modernization does not create something new but accept something new from another nation or other developed country. At first the European elite tried to adapt, then seek the formation of a typical European life in the colony. Bragaweg is a picture of the success of the European elit. The Bragaweg transformation represents economic growth in the region; From the emergence of staple stores to the rise of luxury and industrial goods stores. Modern impression is seen from the lifestyle practiced by the European elite and the full range of facilities and technology in the Bragaweg region. In the war of independence, the sparkling atmosphere of Europe was dimmed and replaced by the atmosphere of war.Keywords: Bragaweg, modern, life style, European elite.